ANALISIS FAKTOR YANG MEMPENGARUHI KELENGKAPAN KODE EXTERNAL CAUSE DI RSUD KABUPATEN BREBES - Tegar Wahyu Yudha Pratama (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2017)
The purpose of this study is to describe the knowledge, attitudes, and ways of doing external cause coding on medical records clerk.This type of research is observational research method. The population used was the officer medical records at hospitals URM Brebes as many as 12 people were taken with total sampling technique.The results of the study are 8 medical records clerk at the level of know (knew) 56.25%, at the level of comprehention (understand) officers 62.5%, the level of applications (apps) 53.12%, at the level of analysis (analysis) 50%, at the level of evaluation (evaluation) 25%. Medical records clerk attitude about charging external cause code officials agree 59.1%, 20.45%, and 20.45% do not agree. Officers take steps in accordance with the rules of ICD-10 as much as 35.71%, because officers used electronic ICD and instant code book. It can be concluded knowledge, attitudes, and the steps of determining a cause external code that officers do not yet good enough.